The Impact of Climate Change on River Alternate Bars. Issue 5 (3rd March 2023) - Redolfi, M.; Carlin, M.; Tubino, M.
Abstract: Climate change is expected to alter the distribution of flow discharge in rivers worldwide. We study the impact of climate‐driven flow changes on the shape of riverbed, and specifically on alternate bars, large deposits of gravel/sand that often form in rivers. We consider the illustrative example of the Alpine Rhine River, showing two nearby reaches with similar hydro‐morphological characteristics, but different channel width. Hydrological projections are obtained from literature, while the evolution of alternate bars is predicted through a novel, semi‐analytical model. Results show a remarkably different behavior of the two reaches: the upstream one, being wide enough for a full development of alternate bars, is resistant to flow alterations; the downstream reach, whose width is close to threshold conditions, is highly susceptible to future changes, showing a strong tendency to increase bar prominence. These findings reflect a general tendency of near‐threshold geomorphic systems to be vulnerable to anthropic stressors. Plain Language Summary: The worldwide alteration of the river flow induced by climate change is likely to significantly impact the bed morphology of embanked rivers, which is often characterized by the presence of alternate bars, namely repetitive sequences of large sediment deposits and scour zones. Bar formation is both a major issue for river management (due to local erosion at instream structures and increase of flood risk), and an important resource for sustaining biodiversity, because bar morphology templates rich habitats for river fauna and vegetation. We analyze the effect of climate change on river bars by considering existing state‐of‐the‐art projections of future flow discharge, and by implementing a mathematical model suitable to perform long‐term simulations, while keeping the essential ingredients to reproduce bar dynamics. Model results reveal a very different adaptation of the riverbed to climate change: relatively wide reaches are expected to maintain the current alternate bar characteristics, while reaches whose width is close to a critical threshold value are likely to experience a remarkable alteration in the next decades, which provides a noteworthy example of how near‐threshold geomorphic systems may be highly sensitive to climate change. Key Points: Climate‐driven changes of hydrological regime can have a significant impact on bar morphology The formation of alternate bars in channelized rivers is promoted by a decrease of frequency of high flows Sensitivity of bar morphology to climatic stressors depends on how far the river width is from the key morphodynamic threshold value